Peningkatan Aktivitas dan Hasil Belajar Biologi Melalui Model Pembelajaran Discovery Learning Siswa Kelas X.IIS.2 SMA Negeri 2 Tilatang Kamang - Hendra Putra (Pendidikan Biologi FKIP UMMY, 2019)
Biology as one of the areas of science, in learning the students acquire a range of learning experiences to understand the concept. One effort to bridge the student activity in order to realize good learning outcomes is through Discovery Learning Model Learning. This study aims to improve the activity and student learning outcomes by using model Discovery Learning on the material in the respiratory system X.IIS.2 class SMA Negeri 2 Tilatang Kamang. This study originated from the fact, that at SMAN 2 Tilatang Kamang learning is often not centered learning, so biology learning process not in accordance with what is expected. The result of study biology is still low with the number of students who have grades below completeness achieve 9 out of 27 students. To solve this problem action learning model Learning.Penelitian Discovery is a Class Action Research (PTK). Classroom Action Research (PTK) is a study that examines the problems that are practical, situational and fundamental. The action taken is real action and dinyakini teacher better than ever. The results showed increased activity and student learning outcomes. Activities that increase is 100% activity observed with very high criteria, information gathering activities of 100% with a very high criteria, discuss with friends 100% with the high criteria, associate 92.59% with a very high criteria, and also mengkumunikasikan 92.59% with very high criteria. But to ask the activity is still relatively low at 37.04%. The results of students in cycle one had an average of 2.81 and an increase in cycle two to 3.02. The number of students who have a value below the limit of completeness in cycle one of 4 people of 27 students, while in the second cycle of all students have a value above the limit set by the thoroughness of the standard curriculum assessment in 2013. Thus the use of the learning model Discovery Learning materials protists system could increase the activity and student learning outcomes in the classroom X.IIS.2 SMAN 2 Tilatang Kamang.